2013
DOI: 10.1016/j.ntt.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Binge toluene exposure in pregnancy and pre-weaning developmental consequences in rats

Abstract: The persistent rate of abuse of inhaled organic solvents, especially among women of child-bearing age, raises the risk for teratogenic effects of maternal toluene abuse. In this study, timed-pregnant Sprague Dawley rats were exposed from Gestation Day (GD) 8 to GD20 to 12,000 or 8,000 parts per million (ppm) toluene, or 0 ppm (controls) for 30 min twice daily, 60 min total daily exposure. Pups were assessed from postnatal day (PN) 4 to PN21 using a developmental battery measuring growth (i.e., body weight), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
(78 reference statements)
2
12
0
2
Order By: Relevance
“…The reduced weight gain in dams after exposure to 12,000-ppm toluene vapor, similar to one of our previous reports (Bowen & Hannigan, 2013), suggests that a toluene-induced maternal toxicity or under-nutrition during pregnancy may have contributed to the current growth restrictions observed in pups at PN1. One the other hand, in another prior study using identical toluene exposures in pregnant rats we reported significant reductions in fetal growth without effects on maternal weight gain (Bowen et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reduced weight gain in dams after exposure to 12,000-ppm toluene vapor, similar to one of our previous reports (Bowen & Hannigan, 2013), suggests that a toluene-induced maternal toxicity or under-nutrition during pregnancy may have contributed to the current growth restrictions observed in pups at PN1. One the other hand, in another prior study using identical toluene exposures in pregnant rats we reported significant reductions in fetal growth without effects on maternal weight gain (Bowen et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Abuse of inhalants like toluene while pregnant can lead to a constellation of physical anomalies and developmental disabilities in the offspring collectively referred to as “Fetal Solvent Syndrome” (FSS; Toutant and Lippmann, 1979, Hannigan and Bowen, 2010, Bowen and Hannigan, 2013). The signs of FSS in children include premature birth, low birth weight (Ahmed and Jaakkola, 2007), skeletal and other facial anomalies (Jones and Balster, 1998), and impaired cognitive development (Laslo-Baker et al, 2004), outcomes sharing similarities with Fetal Alcohol Spectrum Disorders (FASD; Pearson et al, 1994, Wilkins-Haug, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene is one of the most widely used aromatic solvents but is a known carcinogen and teratogen (Bowen & Hannigan, 2013). It is toxic furthermore to the liver and to the hematological and immune systems.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work examining prenatal binge toluene exposure, repeated 15 min (8,000 or 12,000 ppm) exposure twice a day (30 min total per day) from Gestation Day 8 (GD8) through GD20 produced significant increases in total minor and gross malformations, including reduced body weight, soft tissue anomalies (e.g., missing eyes), and skeletal abnormalities (shortened and/or missing digits and missing limbs, reduced skeletal ossification), "runting" and fetal or postnatal death [8,51]. Growth deficits were more prevalent when repeated exposures to high concentrations were increased to 30 min binge exposures in rats [11] and mice [51]. This pattern of prenatal exposure to toluene also resulted in a higher incidence of gross morphological anomalies including shortened and/or missing digits and missing limbs [12].…”
Section: Introductionmentioning
confidence: 99%